Chinese Family Language Policy in The Context of Trilingual Schools in Surabaya - Steffi Thanissa Halim; Budi Kurniawan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Chinese language education is becoming popular in the world, including in Indonesia. Since the end of the New Order government in 1999 and the establishment of the strategic partnership between Indonesia and China in 2005, more and more Indonesians are starting to learn Chinese. Apart from being a foreign language, Chinese is also considered as a heritage language for Chinese Indonesian. With the increasing interest in learning Chinese, trilingual schools that offer Chinese, English, and Indonesian language learning have started to appear in various cities in Indonesia, including in Surabaya. Within the context of trilingual schools, this study uses a qualitative method to explore family language policy (FLP), related to multilingualism and the efforts to preserve the heritage language, in the Surabaya Chinese family. Data were obtained by interviewing eight participants who are parents of trilingual school students from various levels of education: kindergarten, elementary and secondary school. Three core components of FLP, namely: language ideology, language management, and language practice were used as guidance to code the interview data. We found that the language ideology of the parents is linked with the global and economic value of the language and the imagined multilingual person they hope their children to be. The parents consider English and Chinese as the important languages in relation to today’s globalized world. They imagine their children to be multilingual persons who have the necessary linguistic capital for communicating transnationally. But, due to the lack of Chinese and English language skills of the parents, the language practice at home is rather limited to the Indonesian language. They still rely heavily on trilingual schools to provide a language environment and linguistic capital of English and Chinese language. Although parents’ language ideology is supportive of their children being multilingual, it turns out that trilingual schools have a fairly important and central role in forming multilingualism in children.Keywords: family language policy, trilingual schools, Chinese Indonesians